Development of Pain Assessment Tool in Older Adult with Cancer, Nong Bua Lamphu Province Primary Care Unit - Chanchompoo, Sutheera (Journal of Health Science of Thailand, 2019)
The primary care unit of Nong Bua Lamphu Hospital, Nong Bua Lamphu Province, had 95 ageing bed-ridden patients, and among them there were 50 elderly people who were sick with invasive cancer. They were mainly treated in intensive care and returned home for proper home care. The problem associated with the care for petients in this group was the inappropriate pain assessment and management which mainly did not match the type of pain. Based on the problem analysis, two main causes were identified: (1) health personnel had different direction for pain assessment which was generally based on the experiences and the knowledge gain from their training; and (2) the deterioration of the pateints’ organs associated with communication, such as poor vision, poor hearing, and poor reporting of pain. As a result, the pain assessment and management was ineffective and inadequate. Such situation indicated the need for an appropriate tool for pain assessment which required full attention covering all medical and social dimensions. Proper assessment will improve the management of pain which has to keep pace with rapid acceleration of the disease in the elderly. The objective of this study was to develop a pain assessment tool for elderly patients with cancer under the responsibility of Nong Bbua Lumphu primary care unit. The study was conducted by collecting and extracting knowledge and experiences from 10 evidence-based published documents, and developed a tool for pain assessment. The draft was subsequently improved by experts and tried out with some cancer patients in the community. The final version of the pain assessment form was then utilized in the unit. The form was comprised of 3 parts: (1) history of pain, (2) methods of pain assessment in the elderly, and (3) pain assessment in cancer patients. Implementation of the form revealed that (1) the elderly were appropriately assessed and managed (90.0% of the cases), and (2) 96.0% of family health workers were satisfied with the use of the tool.